On approximation of the separately continuous functions 2π-periodical in relation to the second variable - Voloshyn, H.A.; Maslyuchenko, V.K. (Carpathian Mathematical Publications, 2010)
Using Jackson's and Bernstein's operators we prove that for every topological space X and an arbitrary separately continuous function f: X × R→ R, 2π-periodical in relation to the second variable, there exists such sequence of jointly continuous functions f_n: X × R→ R such that functions f_n^x=f_n(x, ·): R→ R are trigonometric polynomials and f_n^x ightrightarrows f^x on R for every xX.